Combination Therapy of Ezetimibe and Rosuvastatin for Dyslipidemia: Current Insights - Chilbert MR; VanDuyn D; Salah S; Clark CM; Ma Q (Dove Medical Press, 2022)
Maya R Chilbert,1,2 Dylan VanDuyn,3 Sara Salah,1 Collin M Clark,1,2 Qing Ma1 1Department of Pharmacy Practice, School of Pharmacy and Pharmaceutical Sciences, University at Buffalo, Buffalo, NY, USA; 2Department of Pharmacy, Buffalo General Medical Center, Buffalo, NY, USA; 3Department of Pharmacy, Buffalo Veterans Affairs Medical Center, Buffalo, NY, USACorrespondence: Maya R Chilbert, Department of Pharmacy Practice, University at Buffalo School of Pharmacy and Pharmaceutical Sciences, 202 Pharmacy Building, Buffalo, NY, USA, Tel +1 716 829-5172, Fax +1 716-829-6093, Email mayahols@buffalo.eduAbstract: Cardiovascular disease is one of the leading causes of death around the world with various efforts being made to reduce risk in patients through preventive measures. One major method for prevention has been managing cholesterol, particularly low-density lipoprotein to decrease atherosclerotic plaque burden, potentially decreasing future cardiac complications. Statins have been the gold standard therapy for hypercholesterolemia treatment due to their ease of dosing, limited drug interactions, and favorable safety profile. Unfortunately, statin therapy alone is not always effective enough to adequately control a patient's elevated lipid levels and combination therapy may be warranted. Ezetimibe is commonly added to regimens to help augment cholesterol lowering by inhibiting the absorption of cholesterol. The recent approval of a combination tablet of high-intensity rosuvastatin and ezetimibe has introduced a potentially more beneficial option for cholesterol management in addition to the only available combination of moderate intensity simvastatin and ezetimibe. We aimed to identify potential beneficial effects of ezetimibe by comparing its use in combination with high-intensity rosuvastatin compared to a statin therapy alone or in combination with moderate intensity simvastatin through a literature review. The current evidence indicated that combination therapy outperformed statin monotherapy in reduction of low-density lipoprotein cholesterol and patients were more likely to achieve their target low-density lipoprotein cholesterol goal level. This suggests rosuvastatin/ezetimibe combination holds a potential place in therapy for patients requiring a more aggressive reduction in cholesterol to help prevent atherosclerotic disease.Keywords: hypercholesterolemia, hyperlipidemia, cardiac events, lipid biomarkers, atherosclerosis